2016
DOI: 10.1590/1982-43272663201609
|View full text |Cite
|
Sign up to set email alerts
|

The Interface Between Quality and Violence in Marital Relationships

Abstract: Domestic violence has been considered accountable for a reduction inthe level of marital quality, although no relationship has been identified between these variables. This study aimed to measure the levels of marital quality and domestic violence, as well as their relationship with sociodemographic characteristics and the predictive power of the different types of violence on martial quality. This quantitative study included 186 heterosexual couples (N = 372), who answered a sociodemographic questionnaire, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 28 publications
1
9
0
6
Order By: Relevance
“…Moreover, it was found that there was gender symmetry in the perpetration of violence, but differences in its frequency. In the same angle, a comprehensive study presented by Razera, Mosmann and Falcke (2016) found that men committed significantly more sexual coercion, while women perpetrated more psychological violence, which could be linked to sociocultural issues. While there may be differences between the types of violence committed, to separately examine the victims and perpetrators may be a bias that influences the results, so it is relevant to do further research and assess this duo.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, it was found that there was gender symmetry in the perpetration of violence, but differences in its frequency. In the same angle, a comprehensive study presented by Razera, Mosmann and Falcke (2016) found that men committed significantly more sexual coercion, while women perpetrated more psychological violence, which could be linked to sociocultural issues. While there may be differences between the types of violence committed, to separately examine the victims and perpetrators may be a bias that influences the results, so it is relevant to do further research and assess this duo.…”
Section: Discussionmentioning
confidence: 98%
“…Aponta-se para a possível naturalização da violência psicológica nas relações conjugais (Razera, Mosmann, & Falcke, 2016), o que gera o não reconhecimento desta como uma tática de resolução de conflitos disfuncional e/ou destrutiva, nas interações entre os subsistemas conjugal ou parental. Esse dado merece especial atenção, visto que altos níveis de agressão psicológica entre o casal estão associados a problemas externalizantes e internalizantes nos filhos (Pendry, Carr, Papp, & Antles, 2013), além de dificuldades de ajustamento escolar (McCoy et al, 2013), apontando para a necessidade de elaboração de estratégias preventivas para o problema (Bhona et al, 2014).…”
Section: Discussõesunclassified
“…Psychological aggression, described in the literature as the most common strategy between spouses, may be considered destructive. This is because it undermines each partner's self-esteem and entails emotional harm (Bolze et al, 2013;Razera, Mosmann, & Falcke, 2016).…”
Section: Parents' and Children's Reactions To Marital Conflict In Thementioning
confidence: 99%